LIMIT EQUILIBRIUM OF CYLINDRICAL SHELL MADE FROM FUNCTIONALLY GRADIENT MATERIAL WITH INTERNAL CRACKS ARBITRARY CONFIGURATION - Николишин, Мирон Михайлович; Ростун, Микола Йосипович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The problem on limit equilibrium elastic-plastic of functionally gradient material (FGM) made cylindrical shell internal crack arbitrary configuration reduced to a system of nonlinear singular integral equations, which is solved, the numerical method of mechanical quadratures.